1-Octanol/water partition coefficients of n-Alkanes from molecular simulations of absolute solvation free energies - Nuno M. Garrido (2009)
The 1-octanol/water partition coefficient is an important thermodynamic variable usually employed to understand and quantify the partitioning of solutes between aqueous and organic phases. It finds widespread use in many empirical correlations to evaluate the environmental fate of pollutants as well as in the design of pharmaceuticals. The experimental evaluation of 1-octanol/water partition coefficients is an expensive and time-consuming procedure, and thus, theoretical estimation methods are needed, particularly when a physical sample of the solute may not yet be available, such as in pharmaceutical screening. 1-Octanol/water partition coefficients can be obtained from Gibbs free energies of solvation of the solute in both the aqueous and the octanol phases. The accurate evaluation of free energy differences remains today a challenging problem in computational chemistry. In order to study the absolute solvation Gibbs free energies in 1-octanol, a solvent that can mimic many properties of important biological systems, free energy calculations for n-alkanes in the range C1-C8 were performed using molecular simulation techniques, following the thermodynamic integration approach. In the first part of this paper, we test different force fields by evaluating their performance in reproducing pure 1-octanol properties. It is concluded that all-atom force fields can provide good accuracy but at the cost of a higher computational time compared to that of the united-atom force fields. Recent versions of united-atom force fields, such as Gromos and TraPPE, provide satisfactory results and are, thus, useful alternatives to the more expensive all-atom models. In the second part of the paper, the Gibbs free energy of solvation in 1-octanol is calculated for several n-alkanes using three force fields to describe the solutes, namely Gromos, TraPPE, and OPLSAA. Generally, the results obtained are in excellent agreement with the available experimental data and are of similar accuracy to commonly used QSPR models. Moreover, we have estimated the Gibbs free energy of hydration for the different compounds with the three force fields, reaching average deviations from experimental data of less than 0.2 kcal/mol for the case of the Gromos force field. Finally, we systematically compare different strategies to obtain the 1-octanol/water partition coefficient from the simulations. It is shown that a fully predictive method combining the Gromos force field in the aqueous phase and the OPLS-AA/TraPPE force field for the organic phase can give excellent predictions for n-alkanes up to C8 with an absolute average deviation of 0.1 log P units to the experimental data. (c) 2009 American Chemical Society.